The Influence of Human Development Index, Unemployment and Poverty on Economic Growth in East Java Province in The Perspective of Islamic Economics in 2014-2023 - Istiadah, Istiadah; Pamuji, Alif Endy; Agustin, Mawadatul Hifniyah (Program Studi Ilmu Ekonomi UIN Sunan Ampel Surabaya, 2025)
Economic development achieved by a country or region can be measured by economic growth. The goal is to know the effect of HDI, Unemployment and Povertiy on Economic Growth in East Java in the Perspective of Islamic Economic. This study uses secondary data from BPS 2014-2023. The research method is quantitative with multiple linear regression using regression using SPSS and Ms. Exel. Research results show HDI has an effect on East Java Economic Growth, sig 0.003 and t count (- 4.683>2.306). Unemployment partially affects East Java Economic Growth, sig 0.001 and t count (-6.149>2.306). Poverty partially affects East Java Economic Growth, sig 0.013 and t count (-3.503>2.306). By together HDI, Unemployment and Poverty affect the Eoconomic Growth of East Java, sig 0.001 and F count (22.59>4.76).